Risk of Low Energy Availability, Disordered Eating, Exercise Addiction, and Food Intolerances in Female Endurance Athletes - Fahrenholtz, Ida Lysdahl; Melin, Anna Katarina; Wasserfurth, Paulina; Stenling, Andreas; Logue, Danielle; Garthe, Ina; Koehler, Karsten; Gräfnings, Maria; Lichtenstein, Mia Beck; Madigan, Sharon; Torstveit, Monica Klungland (Frontiers in Sports and Active Living, 2022)
Relative energy deficiency in sport (RED-S) is a complex syndrome describing health and performance consequences of low energy availability (LEA) and is common among female endurance athletes. Various underlying causes of LEA have been reported, including disordered eating behavior (DE), but studies investigating the association with exercise addiction and food intolerances are lacking. Therefore, the aim of this cross-sectional study was to investigate the association between DE, exercise addiction and food intolerances in athletes at risk of LEA compared to those with low risk. Female endurance athletes, 18-35 years, training ≥5 times/week were recruited in Norway, Sweden, Ireland, and Germany. Participants completed an online-survey comprising the LEA in Females Questionnaire (LEAF-Q), Exercise Addiction Inventory (EAI), Eating Disorder Examination Questionnaire (EDE-Q), and questions regarding food intolerances. Of the 202 participants who met the inclusion criteria and completed the online survey, 65% were at risk of LEA, 23% were at risk of exercise addiction, and 21% had DE. Athletes at risk of LEA had higher EDE-Q and EAI-scores compared to athletes with low risk. EAI-score remained higher in athletes with risk of LEA after excluding athletes with DE. Athletes at risk of LEA did not report more food intolerances (17% versus 10%, P=0.198), but were more frequently reported by athletes with DE (28% versus 11%, P=0.004). In conclusion, these athletes had a high risk of LEA, exercise addiction, and DE. Exercise addiction should be considered as an additional risk factor in the prevention, early detection, and targeted treatment of RED-S among female endurance athletes.